Introduction of Powder Fluxes in Rotary Degassing System Towards Intensifying Refining Process of Aluminium Alloys - M. Piękoś; Z. Smorawiński (Archives of Foundry Engineering)
This paper presents and describes the research capabilities of a prototype experimental bench for realising the composite processing of liquid aluminium alloys by involving gas refining by rotary degassing technology and refining with salts (fluxes) in powder form. The constructed unit was installed in the Experimental Foundry of the Faculty of Foundry Engineering at AGH in the Department of Moulding Processes, Mould Technology, and Non-Ferrous Metals Foundry; it is an integral part of a thyristor-based medium-frequency induction furnace with a melting capacity of up to 60 kg for aluminium alloys. The new experimental bench performs barbotage refining using a rotating head with the possibility of alternating the introduction of refiners/modifiers in powder form. This method can be used in casting lines: continuous in reactors, or batch in ladles. The innovation of the design of the stand and the treatment of the liquid metal with powdered additives consists of dosing the refiner fluid deep into the metal bath through a channel that was made in the rotor axis and the head; this differs from conventional methods in the small amounts of introduced salts and, at the same time, in the very good metal-inert gas-salt homogeneity of the treated metal bath. This method of dosing the refining salts increases the efficiency of their use, reduces any losses, and limits the formation of post-refining slag (thus, minimising the negative environmental effect). The feedstock that was used for the test smelts consisted of recycled materials: aluminium 99.7 (in the form of wires of various cross-sections that were used in electrical engineering – so-called ‘SECTOR’), and the sub-eutectic AlSi7Mg0.3 alloy (in ingot form). The scope of the tests included verifying the technical solutions that were adopted for the dosing of the bulk materials in the form of a fluid, selecting the melting temperature, and dispersing (distributing) the materials in the bath via the rotor head. The results of the trials were reviewed in terms of the changes in the hydrogen content of the performed process and information on such powder-flux-introduction parameters as the type of the rotor head and the melting temperature of the powder flux. Preliminary trials showed that the performed complex refining (rotary degassing + refining with salts being blown as a fluid into the lower parts of the liquid metal) allowed us to reduce the hydrogen content to a level that could not be achieved by gas refining alone.